Evil, virtue, and education in Kant. Issue 13 (10th November 2019) - Formosa, Paul
Abstract: For Kant, we cannot understand how to approach moral education without confronting the radical evil of humanity. But if we start out, as Kant thinks we do, from a morally corrupt state, how can we make moral progress? In response, I explore in this paper Kant's gradualist and revolutionary accounts of moral progress. These differing accounts of progress raise two key questions in the literature: are these accounts compatible and which type of progress comes first? Against other views in the literature, I argue that gradual progress through a change of mores must come first and can gradually lead toward, as its ideal endpoint, a revolution in our disposition (or a change of heart) and the overthrowing of our radical evil. This has important implications for moral pedagogy.